Efficacy of endoscopic interlaminar decompression in lumbar spinal stenosis: a retrospective study - Xiao Qu; Lin Zhang; Zhou xie; Jun Zhang; Yanran Huang; Ningdao Li; Xiaoji Luo (Scientific Reports)
Abstract This retrospective study evaluated the clinical effectiveness of endoscopic interlaminar decompression for lumbar spinal stenosis in 40 patients treated from February 2020 to January 2022. The procedure was successful in all cases, with only one dural sac injury reported and no other complications. Postoperative Visual Analogue Scale (VAS) and Japanese Orthopaedic Association (JOA) scores improved significantly (P<0.05), and the modified Macnab criteria showed an 87.5% rate of excellent and good outcomes at follow-up. No patients required revision surgery. Overall, the endoscopic interlaminar approach proved to be effective, safe, and supported early recovery.